2016
DOI: 10.20471/acc.2016.55.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology of Abdominal Organs – Ten Year Single Center Experience

Abstract: SUMMARY -The aim of the study was to assess the role of fine needle aspiration cytology (FNAC) in the diagnosis of focal changes in solid abdominal organs. A total of 1084 aspirates from intra-abdominal organs including liver, spleen, pancreas and kidneys obtained by ultrasound (US) guidance during a 10-year period were included in the study. The smears were classified as benign, malignant or suspected of malignancy, and unsatisfactory for interpretation. The liver accounted for more than half of the US-guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
6
11
0
Order By: Relevance
“…Causes of cervical lymphadenopathy vary based on age. Overall, benign reactive lymph node aspirates comprise a large portion of the diagnoses in patients from pediatric and adult populations . In concordance to the previous studies, the majority of cases from our series were samplings of benign reactive lymph nodes, totaling 36 of the 48 patients (75%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Causes of cervical lymphadenopathy vary based on age. Overall, benign reactive lymph node aspirates comprise a large portion of the diagnoses in patients from pediatric and adult populations . In concordance to the previous studies, the majority of cases from our series were samplings of benign reactive lymph nodes, totaling 36 of the 48 patients (75%).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, benign reactive lymph node aspirates comprise a large portion of the diagnoses in patients from pediatric and adult populations. [10][11][12][13][14] In concordance to the previous studies, the majority of cases from our series were samplings of benign reactive lymph nodes, totaling 36 of the 48 patients (75%). Nineteen patients had only cytologic assessment without further workup due to minimal clinical concern and did not develop subsequent hematologic malignancies.…”
Section: Discussionsupporting
confidence: 88%
“…FNAC is a simple, reliable and inexpensive diagnostic tool in evaluation of HN swellings. [7][8][9] It causes minimal trauma to the patient and carries virtually no risk of complications. [10][11][12][13][14] It is an outdoor procedure which is safe and well accepted.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that of all peripheral LNs, cervical LNs were most commonly identifi ed by both physicians and patients. In addition, over fi fty percent of lymphadenopathies have been located in the head and neck region [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%